Dampak K-Pop Terhadap Akhlak Bermedia Sosial Pada Mahasiswa Fakultas Ilmu Sosial Universitas Negeri Padang - Muhammad Irfan Maulana; Indah Muliati (Prodi Pendidikan Keagamaan Islam, 2023)
The entry of K-Pop culture has an impact on fans. This research aims to find out in depth how the impact of K-Pop on the morals of fellow human beings in social media, this research is a qualitative research. The research subjects were students of the Faculty of Social Sciences, Padang State University. The data collection method is to interview informants and document them. Based on the results of the study, it was found that 1) The positive impact of K-Pop on the morals of fellow human beings in using social media in Students of the Faculty of Social Sciences, Padang State University, namely a) Increasing relationships, b) Carrying out social actions, c) Be careful in using social media. 2) The negative impact of K-Pop on the morals of fellow human beings in social media on Students of the Faculty of Social Sciences, Padang State University, namely a) Liking comments containing hate speech on social media, b) Doing fanwar or hate comments on social media with inappropriate words , c) Creating anonymous accounts so that they are freer and freer to express themselves on social media and leave no digital footprints.